Pengaruh Sistem Informasi Akuntansi dan Penerapan SAK EMKM terhadap Keberhasilan UMKM - Yohana Aprilita Rosginem Kein; Wilhelmina Mitan; Fransiscus De Romario (Jurnal Mutiara Ilmu Akuntansi, 2024)
The aim of this research is to determine the influence of the Accounting Information System and the Implementation of SAK EMKM on the Success of MSMEs in East Alok District. This research uses a quantitative approach with the nature of explanatory research. The sampling technique used saturated samples with a sample size of 30 people. The data collection technique used a questionnaire distributed to 30 respondents and the data analysis technique used multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 23. From the research results it was found that the variables Accounting Information System (X1) and Implementation of SAK EMKM (X2) influences the success of MSMEs (Y) with positive parameters, which means that the better or higher the level of implementation of the Accounting Information System and EMKM SAK, the higher the level of success of MSMEs. The influence of the Accounting Information System (X1) and the Implementation of SAK EMKM (X2) is 72.9% on the Success of MSMEs (Y) of the Basic Food Kiosk Business in East Alok District, while 27.1% is influenced by other factors outside the research variables.